Pemberdayaan Peternak dalam Teknologi Produksi Pupuk Organik dan Biogas di Desa Gedong dan Desa Gemawang Kecamatan Ngadirojo, Kabupaten Wonogiri - Shanti Emawati; Endang Tri Rahayu; Suwarto Suwarto; Sudiyono Sudiyono (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2020)
Ngadirojo District was one of the centers of beef cattle business development in Wonogiri Regency. But the business done by farmers has not yet produced an optimal income. The purpose of this service activity was to empower farmers by increasing farmers' knowledge through the application of organic fertilizer-based fertilizer production technologies for beef cattle manure and biogas waste so as to increase the income of farmers. The method of this community service activity was through FGD (Focus Group Discussion), counseling, training and demonstration plots on technology for organic fertilizer and biogas production. The result of this activity was an increase in knowledge of farmers after attending counseling and training on organic fertilizer and biogas production technology. Farmers in Gemawang and Gedong Ngadirojo villages have benefited from the construction of biogas installations and the processing of livestock waste into organic fertilizer. The conclusion of this activity was the effort of empowerment through counseling activities and training on processing livestock waste into organic fertilizer and biogas showing success and running effectively as seen from the increasing knowledge of respondents after participating in counseling and training activities.